Analog and digital filter design - Winder, Steve; Winder, Steve (Amsterdam ; Boston : Newnes, 2002)
Unlike most books on filters, Analog and Digital Filter Design does not start from a position of mathematical complexity. It is written to show readers how to design effective and working electronic filters. The background information and equations from the first edition have been moved into an appendix to allow easier flow of the text while still providing the information for those who are interested. The addition of questions at the end of each chapter as well as electronic simulation tools has allowed for a more practical, user-friendly text. *Provides a practical design guide to both analog and digital electronic filters *Includes electronic simulation tools *Keeps heavy mathematics to a minimum.
Introduction; Time And Frequency Response; Poles and Zeroes; Analog Lowpass Filters; Highpass Filters; Bandpass Filters; Bandstop Filters; Impedance Matching Networks; Phase Shift Networks (All-Pass Filters); Selecting Components for Analog Filters; Filter Design Software; Transmission Lines and Printed Circuit Boards as Filters; Filters For Phase Locked Loops; Filter Integrated Circuits; Introduction to Digital Filters; Digital 'Fir' Filter Design; IIR Filter Design; Design Equations.
Rev. ed. of: Filter design. c1997.
Includes bibliographical references (p. [437]-438) and index.
Keywords: Electric filters -- Design and construction; Electronic books